An optimized Algorithm for broadcast beacon frequency and transmission power in VANETs. Issue 1 (March 2020) - Yang, Guoyan; Li, Xiangfeng; Shi, Haiyang
Abstract: Power control has been an important branch of the research field for VANETs. In order to meet the safety of vehicle driving, Vehicle-to-Vehicle(V2V) communication has become a research hotpot simultaneously. In the internet of vehicles, most of the messages generated by V2V communication are implemented by broadcasting. This paper proposed a joint optimization algorithm for power control and broadcast beacon frequency based on the LTE-V2V communication protocol. This algorithm applies deep reinforcement learning (DRL) and designs a reward function that can represent the communication effect of LTE-V2V. The experimental results show that the proposed algorithm can better configure the transmitting power and broadcast beacon frequency of the vehicle terminal, and obtain more reliable communication effects in the dynamic traffic flow environment.